Contemporary Issues and Challenges in the Indian Education System - Bhuwan Gupta; Sweety Dubey (International Journal of Engineering and Management Research, 2019)
Education is the root of each nation. A nation won't have the capability to make due in the alert world, if its guidance framework isn't fit for contributing for its enhancement. Indian training framework is broadly criticized in multi-measurements for its inability to make required employability in its understudies as per the business prerequisites and its failure to add to comprehensive development in the country all in all. This paper deeds to feature the issues and give a few answers for purpose them. The study utilizes optional information from different accessible sources. The analyst presumes that the issues in the present training framework that are overwhelming the development of this nation can be handled successfully if helpful and submitted moves are made by the Government to determine them.